Response of Sowing Dates, Crop Establishment Methods and Mulching on Growth, Productivity and Profitability of Spring Wheat at Rampur, Chitwan, Nepal - Aryal, Amrit; Anil Balchhaudi; Khadka, Rabin; Kumar Sah, Shrawan; Marahatta, Santosh; Parajuli, Tulsi (International Journal of Applied Sciences and Biotechnology, 2022)
Intensive tillage with no crop residue after rice harvest in conventional wheat cultivation increases the turn around time, delays sowing and affects the yield. A field experiment was carried out to assess the effect of sowing dates, establishment methods and mulching and their interaction on growth, productivity and profitability of spring wheat at agronomy farm of AFU, Rampur Chitwan, Nepal from November 2020 to April 2021. The experiment was laid out in strip-split plot design, with three dates of sowing (20th November, 5th December and 20th December) in vertical plots, two establishment methods (Zero tillage and Conventional tillage) in horizontal plots and two levels of mulching (0 t ha-1 and 5 t ha-1 of rice straw mulch) in sub-plots and replicated thrice with Vijay as test variety. Data regarding the phenology, growth parameters, yield attributes and yield were recorded, analyzed and presented. The research results revealed that date of sowing and mulching significantly influenced phenology, growth, yield attributes, yield and their interactions. The higher grain yield was obtained in 5th December as well as 20th November sowing in conventional tillage with mulch (4511.49 & 4492.12 kg ha-1 respectively). These grain yields were statistically at par with 5th December and 20th November sowing in zero tillage with mulch (4363.74 & 4129.97 kg ha-1 respectively). Net return and B:C ratio were significantly higher on 5th December and 20th November sowing with mulch in zero tillage than 20th December sowing in conventional tillage without mulch. Int. J. Appl. Sci. Biotechnol. Vol 10(4): 237-244.